Low-Expressing Synucleinopathy Mouse Models Based on Oligomer-Forming Mutations and C-Terminal Truncation of α-Synuclein - Martinez Hernandez, Ana; Silbern, Ivan; Geffers, Insa; Tatenhorst, Lars; Becker, Stefan; Urlaub, Henning; Zweckstetter, Markus; Griesinger, Christian; Eichele, Gregor (Frontiers in Neuroscience, 2021)
α-synuclein (αSyn) is the main protein component of Lewy bodies, intracellular inclusions found in the brain of Parkinson’s disease (PD) patients. Neurotoxic αSyn species are broadly modified posttranslationally and, in patients with genetic forms of PD, carry genetically encoded amino acid substitutions. Mutations and C-terminal truncation can increase αSyn oligomerization and fibrillization. Although several genetic mouse models based on αSyn mutations and/or truncations exist, there is still a lack of mouse models for synucleinopathies not relying on overexpression. We report here two synucleinopathy mouse models, which are based on a triple alanine to proline mutation (TP) and a truncation (Δ119) of αSyn, but do not overexpress the protein. We knocked hαSynTP or hαSynΔ119 (h stands for “human”) into the murine αSyn locus. hαSynTP is a structure-based mutant with triple alanine to proline substitutions that favors oligomers, is neurotoxic and evokes PD-like symptoms in Drosophila melanogaster. hαSynΔ119 lacks 21 amino acids at the C-terminus, favors fibrillary aggregates and occurs in PD. Knocking-in of hαSynTP or hαSynΔ119 into the murine αSyn locus places the mutant protein under the control of the endogenous regulatory elements while simultaneously disrupting the mαSyn gene. Mass spectrometry revealed that hαSynTP and hαSynΔ119 mice produced 12 and 10 times less mutant protein, compared to mαSyn in wild type mice. We show phenotypes in 1 and 1.5 years old hαSynTP and hαSynΔ119 mice, despite the lower levels of hαSynTP and hαSynΔ119 expression. Direct comparison of the two mouse models revealed many commonalities but also aspects unique to each model. Commonalities included strong immunoactive state, impaired olfaction and motor coordination deficits. Neither model showed DAergic neuronal loss. Impaired climbing abilities at 1 year of age and a deviant gait pattern at 1.5 years old were specific for hαSynΔ119 mice, while a compulsive behavior was exclusively detected in hαSynTP mice starting at 1 year of age. We conclude that even at very moderate levels of expression the two αSyn variants evoke measurable and progressive deficiencies in mutant mice. The two transgenic mouse models can thus be suitable to study αSyn-variant-based pathology in vivo and test new therapeutic approaches.